The Laser Active Element Based on Dye on Porous Alumina - Zeinidenov, A.K.; Ibrayev, N.Kh.; Aimukhanov, A.K. (KarU, 2014)
Luminescent properties of Rhodamine 6G in porous alumina matrix have been investigated. From the SEM images the pore diameter is determined to be ~ 50 nm and the distance between the pores to be about 250 nm. Specific surface area of nanoporous alumina films measured by gas adsorption (BET method) was 6 m2/g. Absorption and fluorescence spectra of Rhodamine 6G embedded in pores of anodic alumina oxide were measured. Decreasing of absorbance of monomers was observed upon increasing of Rhodamine 6G concentrations. At the same time appearing of new maximum at the short-wavelength part as a result of formation of dimer of dye was registered. Increasing of concentration of dye molecules in the pores leads to quenching of fluorescence of Rhodamine 6G. The lasing characteristics were examined upon excitation of the samples by second harmonic Nd: YAG laser λgen = 532 nm, Еimp = 90 mJ, τ = 10 ns in the longitudinal form. The dye generation spectra in nanoporous alumina under different power densities of the pump source were measured. It is established that when the pumping source power is 0.4 MW/cm2 on the background spectrum of laser - induced fluorescence the narrow strip of the laser emission with a peak wavelength of 572 nm appears. Further increase in the power density of the pumping source leads to a narrowing of the band of generation and an increase in its intensity. The obtained results demonstrate the potential of using nanoporous alumina for creating the active elements of quantum electronics.
Keywords: Porous Alumina; Laser Active Element; Dye